Staphylococcal Sepsis with Multiple Abscesses, Urinary Tract Infection, and Bilateral Renal Vein Thrombosis in a Patient with Uncontrolled Diabetes Mellitus. (11th October 2012) - Khan, Malik A. A.; Hunter, Jonathan Michael; Tan, Christopher; Seleem, Mostafa; Stride, Peter J. O.
Abstract : We report a case of staphylococcal sepsis with vascular complications including peripheral emboli and renal vein thrombosis. Bilateral renal vein thrombosis has not been reported as a complication of Staphylococcus aureus (SA) axillary abscess. Uncontrolled diabetes was the only detected predisposing medical condition. The patient was treated successfully with incision and drainage of soft-tissue abscesses and intravenous antibiotic for six weeks and with anticoagulation for renal vein thrombosis.